Pentingnya Sertifikasi Halal dalam Perspektif Etika Bisnis Islam terhadap Produk Makanan Halal - Bastomi, Rakhma Diana; Oktaviany, Mega; Wandini, Evi Ayu; Shavira, Lely; Hasanudin, Qhonsa Nafisa; Syarifudin, Syarifudin (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Halal certification is crucial for consumers, especially Muslim consumers, which is why in Indonesia, there are institutions whose role is to ensure that consumer products, such as food, beverages, and medicines are in accordance with Islamic law, namely the Majelis Ulama Indonesia (MUI) and Badan Pengawas Obat dan Makanan (BPOM). Halal certification not only reflects compliance with Islamic ethical principles, but also builds consumer confidence and supports economic growth based on morals and spirituality. The purpose of this research is to find out how important the inclusion of halal labels on every product circulated by producers. The method used in this research is a qualitative method with systematic literature review technique. The result of this study is the achievement of an increase in producer awareness regarding the importance of halal labels for producers and consumers, so as to achieve a society that is literate in the importance of halal certification.